According To The National Personnel Training Program Changes In The Primary Education System And Problems Of Strengthening Base Of Material And Technical - Furqat Kadirjan ugli Isoqjanov (Zien Journals, 2025)
In this article, it is explained that primary education is the most important part of the reforms within the framework of the National Personnel Training Program and is of great importance in creating a solid foundation of knowledge for the country’s young generation
Keywords: Constructive management; national personnel training program; interactive teaching methods